Contemporary endovascular management of splenic vascular pathologies. Issue 12 (December 2020) - Leung, E.; Maingard, J.; Yeh, J.; Lee, M.J.; Brooks, D.M.; Asadi, H.; Burrows, D.A.; Kok, H.K.
Abstract : The spleen is a commonly injured organ and the splenic vasculature is also susceptible to inflammation and trauma, often resulting in aneurysm formation. Splenic artery aneurysms carry a high risk of rupture and are associated with high mortality and morbidity. Due to the advances in endovascular techniques and devices, endovascular management of splenic vascular pathologies is now considered a first-line strategy. Endovascular embolisation and advance techniques including balloon- or stent-assisted coil embolisation enables minimally invasive management option while preserving splenic function.